Going the distance: Mapping mobility in the Kalahari Desert during the Middle Stone Age through multi-site geochemical provenancing of silcrete artefacts. Issue 96 (July 2016) - Nash, David J.; Coulson, Sheila; Staurset, Sigrid; Ullyott, J. Stewart; Babutsi, Mosarwa; Smith, Martin P.
Abstract: This study utilises geochemical provenancing of silcrete raw materials, in combination with chaîne opératoire analyses, to explore lithic procurement and behavioural patterns in the northern Kalahari Desert during the Middle Stone Age (MSA). New data from the sites of Rhino Cave, Corner Cave, and ≠Gi in northwest Botswana, combined with earlier results from White Paintings Shelter, reveal that the long distance transport of silcrete for stone tool manufacture was a repeated and extensively used behaviour in this region. Silcrete was imported over distances of up to 295 km to all four sites, from locations along the Boteti River and around Lake Ngami. Significantly, closer known sources of silcrete of equivalent quality were largely bypassed. Silcrete artefacts were transported at various stages of production (as partially and fully prepared cores, blanks, and finished tools) and, with the exception of ≠Gi, in large volumes. The import occurred despite the abundance of locally available raw materials, which were also used to manufacture the same tool types. On the basis of regional palaeoenvironmental data, the timing of the majority of silcrete import from the Boteti River and Lake Ngami is constrained to regionally drier periods of the MSA. The results of our investigation challenge key assumptions underlying predictive models of human mobility that use distance–decay curves and drop-off rates. Middle Stone Age peoples in the Kalahari appear to have been more mobile than anticipated, and repeatedly made costly choices with regard to both raw material selection and items to be transported. We conclude that (i) base transport cost has been overemphasised as a restrictive factor in predictive models, and (ii) factors such as source availability and preference, raw material quality, and potential sociocultural influences significantly shaped prehistoric landscape use choices.